Algorithmic Aspects of k-Geodetic Sets in Graphs - A. Anto Kinsley; K. Karthika (International Journal of Mathematics And its Applications, 2016)
Let G be a connected graph of order p2. We study about the geodetic sets and k-geodetic sets of G. We study link vectors and prove a theorem to develop an algorithm to find the k-geodetic sets. Initially we study algorithms to find the closed interval between any two vertices of G and to find it's link vectors. In this paper we present two algorithms to check whether a given set of vertices is a k-geodetic set and to find the minimum k-geodetic set of G.